Comprehensive Pan-Cancer Analysis of Senescence With Cancer Prognosis and Immunotherapy - Zhao, Qinfei; Hu, Weiquan; Xu, Jing; Zeng, Shaoying; Xi, Xuxiang; Chen, Jing; Wu, Xiangsheng; Hu, Suping; Zhong, Tianyu (Frontiers in Molecular Biosciences, 2022)
Senescence is a double-edged sword in tumorigenesis and affects the immunotherapy response through the modulation of the host immune. However, a comprehensive analysis of the senescence-related genes (SRGs) in human cancers is currently lacking, and the predictive role of senescence in cancer immunotherapy response remains unexplored. We used multi-omics approaches to conduct a systematic pan‐cancer genomic analysis of SRGs in cancer. In addition, we calculated the generic senescence score (SS) to quantify the senescence levels in cancers and explored the correlations of SS with cancer prognosis, biological processes, and tumor microenvironment (TME). The gene signatures were deregulated in multiple cancers and indicated context-dependent correlation with prognosis, tumor-immune evasion, and response to therapy across various tumor types. Further analysis disclosed that SS was positively associated with the infiltration levels of immune suppressive cells, including induced Tregs (iTregs), central memory Ts (Tcms), and natural Tregs (nTregs), and negatively associated with immune killer cells, including natural killers (NKs) and mucosal-associated invariant Ts (MAITs). Moreover, the SS was significantly correlated with tumor-associated macrophages (TAMs), cancer-associated fibroblasts (CAFs), immune-related genes, and immune checkpoints, and had a predictive value of immunotherapy response. Finally, the expression of SRGs was involved in resistance to several anticancer drugs. Our work illustrates the characterization of senescence across various malignancies and highlights the potential of senescence as a potential biomarker of the response to immunotherapy.